Every base matters: assessing small subunit rRNA primers for marine microbiomes with mock communities, time series and global field samples. (14th October 2015) - Parada, Alma E.; Needham, David M.; Fuhrman, Jed A.
Summary: Microbial community analysis via high‐throughput sequencing of amplified 16S rRNA genes is an essential microbiology tool. We found the popular primer pair 515F (515F‐C) and 806R greatly underestimated (e.g. SAR11) or overestimated (e.g. Gammaproteobacteria) common marine taxa. We evaluated marine samples and mock communities (containing 11 or 27 marine 16S clones), showing alternative primers 515F‐Y (5′‐GTGY CAGCMGCCGCGGTAA) and 926R (5′‐CCGYCAATTYMTTTRAGTTT) yield more accurate estimates of mock community abundances, produce longer amplicons that can differentiate taxa unresolvable with 515F‐C/806R, and amplify eukaryotic 18S rRNA. Mock communities amplified with 515F‐Y/926R yielded closer observed community composition versus expected (r 2 = 0.95) compared with 515F‐Y/806R (r 2 ∼ 0.5). Unexpectedly, biases with 515F‐Y/806R against SAR11 in field samples (∼4–10‐fold) were stronger than in mock communities (∼2‐fold). Correcting a mismatch to Thaumarchaea in the 515F‐C increased their apparent abundance in field samples, but not as much as using 926R rather than 806R. With plankton samples rich in eukaryotic DNA (> 1 μm size fraction), 18S sequences averaged ∼17% of all sequences. A single mismatch can strongly bias amplification, but even perfectly matched primers can exhibit preferential amplification. We show that beyond in silico predictions, testing with mock communities and field samples is important in primer selection.